Chapter 6 MARINE BIODIVERSITY IN KOREA: A REVIEW OF MACROZOOBENTHIC ASSEMBLAGES, THEIR DISTRIBUTIONS, AND LONG-TERM COMMUNITY CHANGES FROM HUMAN IMPACTS - JONG SEONG KHIM; CHANGKEUN LEE; SUNG JOON SONG; HANNA BAE; JUNSUNG NOH; JUNGHYUN LEE; HYEONG-GI KIM; JIN-WOO CHOI (Taylor & Francis, 2021)
oceanography, climate change, reefs, marine science, marine conservation, marine research
English[eng]
Keywords: bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; bic Book Industry Communication; oceanography, climate change, reefs, marine science, marine conservation, marine research